Design, Synthesis and Antimicrobial Properties of New Tetracyclic Quinobenzothiazine Derivatives - Kisiel-Nawrot, Ewa; Pindjakova, Dominika; Latocha, Malgorzata; Bak, Andrzej; Kozik, Violetta; Suwinska, Kinga; Sochanik, Aleksander; Cizek, Alois; Jampilek, Josef; Zięba, Andrzej (International journal of molecular sciences, 2022)
A new method for modifying the structure of tetracyclic quinobenzothiazinium derivatives has been developed, allowing introduction of various substituents at different positions of the benzene ring. The method consists of reacting appropriate aniline derivatives with 5,12-(dimethyl)thioquinantrenediinium bis-chloride. A series of new quinobenzothiazine derivatives was obtained with propyl, allyl, propargyl and benzyl substituents in 9, 10 and 11 positions, respectively. The structure of the obtained compounds was analyzed by 1H and 13C NMR (HSQC, HMBC) and X-ray analysis. All the compounds were tested against reference strains Staphylococcus aureus ATCC 29213 and Enterococcus faecalis ATCC 29212, and representatives of multidrug-resistant clinical isolates of methicillin-resistant S. aureus (MRSA) and vancomycin-resistant E. faecalis (VRE). In addition, all the compounds were evaluated in vitro against Mycobacterium smegmatis ATCC 700084 and M. marinum CAMP 5644. 9-Benzyloxy-5-methyl-12H-quino [3,4-b][1,4]benzothiazinium chloride (6j), 9-propoxy-5-methyl-12H-quino[3,4-b][1,4]benzothiazinium chloride (6a) and 9-allyloxy-5-methyl-12H-quino[3,4-b][1,4]benzothiazinium chloride (6d) demonstrated high activity against the entire tested microbial spectrum. The activities of the compounds were comparable with oxacillin, tetracycline and ciprofloxacinagainst staphylococcal strains and with rifampicin against both mycobacterial strains. Compound 6j had a significant effect on the inhibition of bacterial respiration as demonstrated by the MTT assay. The compounds showed not only bacteriostatic activity, but also bactericidal activity. Preliminary in vitro cytotoxicity screening of the compounds performed using normal human dermal fibroblasts (NHDF) proved that the tested compounds showed an insignificant cytotoxic effect on human cells (IC50 > 37 μM), making these compounds interesting for further investigation. Moreover, the intermolecular similarity of novel compounds was analyzed in the multidimensional space (mDS) of the structure/property-related in silico descriptors by means of principal component analysis (PCA) and hierarchical clustering analysis (HCA), respectively. The distance-oriented structure/property distribution was related with the experimental lipophilic data.
Keywords: Mycobacterium; Microbial Sensitivity Tests; lidé; mikrobiální testy citlivosti; chloridy; antibakteriální látky; Anti-Bacterial Agents; Chlorides; Methicillin-Resistant Staphylococcus aureus; methicilin rezistentní Staphylococcus aureus; Humans